2021
DOI: 10.3390/ijms22052715
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Polarization in Cardiac Tissue Repair Following Myocardial Infarction

Abstract: Cardiovascular disease is the leading cause of mortality and morbidity around the globe, creating a substantial socio-economic burden as a result. Myocardial infarction is a significant contributor to the detrimental impact of cardiovascular disease. The death of cardiomyocytes following myocardial infarction causes an immune response which leads to further destruction of tissue, and subsequently, results in the formation of non-contractile scar tissue. Macrophages have been recognized as important regulators … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 111 publications
1
85
0
Order By: Relevance
“…PTPRE-AS1 deficiency enhanced PTPRE expression by regulating WDR5-dependent H3K4me3 and, hence, promoted IL-4-stimulated M2 macrophage polarization [ 25 ]. Reparative M2 macrophages have been found to be involved in tumor proliferation and fibrosis [ 26 ]. We found that the expression of PTPRE-AS1 significantly decreased in Hdc −/− mice post MI and increased in RAW264.7 with histamine treatment, which implied that PTPRE-AS1 may play a role in monocyte/macrophage-dependent susceptibility to carcinogenesis [ 6 ] and heart fibrosis [ 10 ] in Hdc −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…PTPRE-AS1 deficiency enhanced PTPRE expression by regulating WDR5-dependent H3K4me3 and, hence, promoted IL-4-stimulated M2 macrophage polarization [ 25 ]. Reparative M2 macrophages have been found to be involved in tumor proliferation and fibrosis [ 26 ]. We found that the expression of PTPRE-AS1 significantly decreased in Hdc −/− mice post MI and increased in RAW264.7 with histamine treatment, which implied that PTPRE-AS1 may play a role in monocyte/macrophage-dependent susceptibility to carcinogenesis [ 6 ] and heart fibrosis [ 10 ] in Hdc −/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…The former type is more capable of differentiating into M1 macrophages, which propagate inflammation, while the latter subset of monocytes gives rise mostly to reparative M2 macrophages ( Figure 1 ). Nevertheless, as with other tissues, an attempt to describe skin macrophages as M1 and M2 phenotypes is probably an oversimplification since a wider range of phenotypes exist [ 67 , 68 ].…”
Section: Acute Wound Healingmentioning
confidence: 99%
“…This presented as reinforced connective tissue structure formation, enhanced microvascular growth, and impaired cardiomyocyte hypertrophy [53]. Many other approaches, including transplantation with human umbilical cord blood mesenchymal stem cells [54] or injection of exosomes from adipose-derived mesenchymal stem cells [55], have been used to promote M2 macrophage polarisation post-MI and resulted in improved cardiac tissue repair in MI models (see review [56]).…”
Section: Monocyte/macrophages: Cells Involved In Both Inflammation and Its Resolutionmentioning
confidence: 99%